Sherbrooke : sa place dans la vie de relations des Cantons de l’Est - Cazalis, Pierre (Cahiers de géographie du Québec, 1964)
Because they are due to economic contingencies rather than to unfavourable natural conditions, present-day regional disparities compel the geographer to modify his concept of the region. Whereas in the past the region was considered essentially as a physical entity, to many authors it appears today to be « a functional area, based on communication and exchange, and as such defined less by its limits than by its centre » (Juillard). It is this concept which will be used in regional planning. Taking the city of Sherbrooke as a nodal centre, the author attempts to define such a region through an analysis and graphical representation of the complementary roles in influence and attraction played by the city in the fundamental aspects of employment, trade, finance, education, communication, health and government. Although it is already well-developed in the secondary sector, with more than 9,000 workers employed in industry and an annual production worth more than $100 million, Sherbrooke bas a power of attraction and influence which is due essentially to its tertiary sector : wholesale trade, insurance, education, communication. Ac-cording to the criteria mentioned above, the area dominated by Sherbrooke includes the whole of the following counties : Sherbrooke, Stanstead, Richmond, Wolfe and Compton ; and the greater part of Frontenac, Mégantic, Artbabaska, Drummond and Brome counties. Shefford and Bagot counties are dominated by Montréal to the west and by Sherbrooke to the east.